Kisvárosi funkciók vizsgálata a Délkelet-Alföld egyik településcsoportján - Zsótér, Brigitta (Jelenkori Társadalmi és Gazdasági Folyamatok, 2011)
In my thesis the functions of four provincial towns in the south-east of the Great Hungarian Plain, According to the article by Zoltán Dövényi and Zoltánné Dövényi (1982) published in “ Békési Élet” the urban functions were attended to by the four settlem ents - Battonya, Medgyesegyháza, Mezőhegyes, Mezőkovácsháza - collectively. Although Tótkomlós is not mentioned in the article, it is important to examine because of its geographical proximity. In the course of my literary overview I outline the indispensable technical know ledge of the topic and the necessary methods applied in my research. The bases of my study were the research methods of Sándor Kókai, conducted in Szabolcs - Szatmár-Bereg county. In my research I have come to the conclusion that the diversification remained but the functions have expanded to a certain extent.